2005
DOI: 10.1016/j.hrtlng.2004.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Two-year follow-up of quality of life in patients referred for heart transplant

Abstract: Our results support the need for ongoing HRQOL assessment with an emphasis on timely recognition and treatment of psychologic distress throughout the heart failure illness trajectory. Heart transplant recipients and candidates equally need special attention and follow-up because they both seem to have emotional and psychologic repercussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…In contrast, some studies found correlations between quality of life and demographic data (Grady et al 1995;Gottlieb et al 2004;Evangelista et al 2005). In their study Evangelista et al (2005) found a restriction of SF36, Study 36-item short form survey; MLHFQ, Minnesota living with heart failure questionnaire; pVO 2 , peak VO 2 ; 6 MWT, Six minute walk test; NYHA, New York heart a s s o c i a t i o n c l a s s i fi c a t i o n ; B D I , b e c k depression inventory; STAI, Spielberger's state-trait anxiety inventory. both physical and mental health and an increase in depression in older female patients with endstage HF.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, some studies found correlations between quality of life and demographic data (Grady et al 1995;Gottlieb et al 2004;Evangelista et al 2005). In their study Evangelista et al (2005) found a restriction of SF36, Study 36-item short form survey; MLHFQ, Minnesota living with heart failure questionnaire; pVO 2 , peak VO 2 ; 6 MWT, Six minute walk test; NYHA, New York heart a s s o c i a t i o n c l a s s i fi c a t i o n ; B D I , b e c k depression inventory; STAI, Spielberger's state-trait anxiety inventory. both physical and mental health and an increase in depression in older female patients with endstage HF.…”
Section: Discussionmentioning
confidence: 91%
“…Most of the studies show that functional capacity defi ciencies affect physical aspects of quality of life (Westlake et al 2002;Carels 2004;Jeng et al 2004;Myers et al 2006). Evangelista et al (2005) found that function limitations had negative impact on the mental health and emotional well-being in the end-stage HF patients. Our study did not reveal any decrease in functional capacity among individuals who had depressive symptoms, either.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the indication for HT represents the possibility of survival and improvement in the quality of life [2,16]: I was disillusioned, and when I saw this light at the end of the tunnel I felt a great joy. I was taking five medications and did not improve, had no perspective on life.…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies have examined in depth psychosocial adjustment and quality of life in heart transplant recipients (Mai, McKenzie, & Kostuk, 1990;Evangelista et al, 2005) However, quality of life (QOL) and patients' well-being are closely associated to increased morbidity and mortality and thus efforts to better understand the QOL and psychological well-being of heart transplant recipients are needed (Evangelista et al, 2003;Myaskovsky et al, 2006). In depth exploration of psychological and emotional factors that may impact to recipients' life is important to the overall improvement of the heart transplant patient's quality of life (Duitsman & Cychosz, 1993;Rybarczyk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%